2006
DOI: 10.1007/s11060-005-9081-1
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL-receptor expression is an independent prognostic factor for survival in patients with a primary glioblastoma multiforme

Abstract: TRAIL-R1 and TRAIL-R2 expression on tumor cells are independent prognostic factors for survival in patients with a glioblastoma multiforme. Both receptors could be targets for TRAIL therapy. As TRAIL-R2 is more expressed, in comparison with TRAIL-R1, on GBM tumor cells, TRAIL-R2 seems to be of more importance as a target for future TRAIL therapy than TRAIL-R1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…The study of Kuijlen et al reports a significant higher expression of TRAIL-R2 than TRAIL-R1 in glioblastomas. 42 In our study, we observed a tendency (p = 0.07) of high TRAIL-R2 levels to independently predict a better clinical outcome of patients with diffuse (WHO grade II) and anaplastic (WHO grade III) gliomas. Accordingly, the study of Kuijlen et al reports that TRAIL-R2 expression is an independent prognostic marker for survival in patients with glioblastomas.…”
Section: © 2 0 0 9 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 49%
“…The study of Kuijlen et al reports a significant higher expression of TRAIL-R2 than TRAIL-R1 in glioblastomas. 42 In our study, we observed a tendency (p = 0.07) of high TRAIL-R2 levels to independently predict a better clinical outcome of patients with diffuse (WHO grade II) and anaplastic (WHO grade III) gliomas. Accordingly, the study of Kuijlen et al reports that TRAIL-R2 expression is an independent prognostic marker for survival in patients with glioblastomas.…”
Section: © 2 0 0 9 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 49%
“…[14][15][16][17] As many chemotherapeutics induce TRAIL-R1/-R2, considerable attention has been given to therapeutic strategies that combine these agents with TRAIL or TRAIL-R1/-R2 agonistic antibodies. In individuals with glioblastoma mulitforme, expression of TRAIL-R1 and TRAIL-R2 are independent prognostic indicators of patient survival, 36 suggesting that these death receptors play an active role in tumor suppression in this setting. Our data show that pharmacological inhibition of Aurora B induces TRAIL-R2 concomitant with TRAIL sensitization in a subset of human glioma cell lines secondary to polyploidization and further suggest that inhibition of Aurora B may be an effective means to sensitize glioblastoma multiforme to TRAIL-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…TNFRSF10C expression is often down regulated in cancer (13)(14)(15), and loss of TNFRSF10C sensitizes cells to TRAIL-induced apoptosis (18). Indeed, TRAIL genes are prognostic for response to chemotherapy and overall survival in patients with CRC, and moreover are prognostic for outcome in patients with other cancers, including glioblastoma multiforme and breast cancer (19)(20)(21)(22)(23)(24). Differences in TRAIL expression in cancers compared with normal cells have led to clinical trials targeting TRAIL-induced apoptosis in CRC, but the genetic profiles of patients were not used as part of the selection criteria (25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%